Peningkatan Kepedulian dan Tanggung Jawab Siswa terhadap Kebersihan Lingkungan Sekolah Berbasis Participatory Action Research - Iiq faiqotul Hima; Maritza Khansa Fauzan; Itsna Amilatul Hasanah; Novena Ade Fredyarini Soedjiwo (Jaanur Elbarik Indonesia, 2026)
This community service research aims to enhance students’ awareness and responsibility in maintaining school environmental cleanliness at MI Istana Hati through a Participatory Action Research (PAR) approach. The study employed a qualitative PAR method involving students, teachers, and school stakeholders in all stages of the program, including problem identification, action planning, implementation, observation, and reflection. Data were collected through direct observation, documentation, and participatory reflection activities. The results show that the initial condition of school cleanliness was inadequate, as indicated by scattered waste, limited sanitation facilities, and low student awareness of cleanliness responsibilities. After the implementation of participatory activities, including environmental cleanliness socialization, the Kotak Ide Bersih program, educational poster installation, and collaborative Sabtu Bersih activities, significant improvements were observed. Students demonstrated increased discipline in disposing of waste properly, greater participation in classroom and school cleaning activities, and higher initiative in maintaining cleanliness without continuous teacher supervision. These findings indicate that the PAR approach effectively strengthens students’ sense of ownership, responsibility, and environmental awareness. In conclusion, participatory based community service activities not only improve the physical condition of the school environment but also contribute to sustainable character development among students, particularly in terms of discipline, responsibility, and environmental care.